Drug‐conjugated polymers as gene carriers for synergistic therapeutic effect. Issue 4 (15th October 2015) - Pofali, P. A.; Singh, B.; Dandekar, P.; Jain, R. D.; Maharjan, S.; Choi, Y. J.; Arote, R. B.; Cho, C. S.
Abstract: The ability to safely and effectively transfer gene into cells is the fundamental goal of gene delivery. In spite of the best efforts of researchers around the world, gene therapy has limited success. This may be because of several limitations of delivering gene which is one of the greatest technical challenges in the modern medicine. To address these issues, many efforts have been made to bind drugs and genes together by polymers for co‐delivery to achieve synergistic effect. Usually, binding interaction of drugs with polymers is either physical or chemical. In case of drug‐polymer physical interaction, the efficiency of drugs generally decreases because of separation of drugs from polymers in vivo whenever it comes in contact with charged biofluid/s or cells. While chemical interaction of drug–polymer overcomes the aforementioned obstacle, several problems such as steric hindrance, solubility, and biodegradability hinder it to develop as gene carrier. Considering these benefits and pitfalls, the objective of this review is to discuss the possible extent of drug‐conjugated polymers as safe and efficient gene delivery carriers for achieving synergistic effect to combat various genetic disorders. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 698–711, 2016.